Computational Intelligence and Load To Source Ratio Index Based Technique for Voltage Security Restoration - Ismail, Muhammad Naqiyuddin; Halim, Mazliza Abdul; Musirin, Ismail; Kasinathan, Vinothini; Mustapha, Aida; Zulkefle, Habibah (International Journal of Integrated Engineering, 2025)
Voltage security remains a critical concern in power systems, as voltage instability can lead to service disruptions and cascading failures. This paper presents an advanced computational intelligence technique based on the load-to-source ratio index, integrated with Evolutionary Programming (EP) to enhance voltage stability. Unlike conventional methods, this approach optimizes reactive power dispatch (ORPD) across multiple configurations to improve voltage levels throughout the network. The technique was validated on the IEEE-30 Bus Reliability Test System under various loading conditions. Results show significant improvements in the index for weak buses, with an increase from 10.9667 to 24.3144 at the critical Bus 29, leading to improved voltage levels across the system. Additionally, the method offers enhanced flexibility by assessing multiple ORPD scenarios, allowing system operators to choose the optimal configuration for different network conditions. These findings suggest that the proposed method not only improves voltage security but also provides a robust, adaptable solution for practical power system operations.